Human Resources Strategy in The Implementation of Electronic Medical Records in Hospitals: Literature Review - Lalu Zulhirsan; Qurratul Aini (Postgraduate, University of Mataram, 2025)
Electronic Medical Records (EMR) represent a digital transformation aimed at enhancing the efficiency and effectiveness of healthcare services. However, EMR implementation faces significant challenges, particularly in the human resources (HR) domain, such as a lack of technical competence and resistance to change. This study aims to identify the barriers and strategies for EMR implementation from an HR perspective. This study employed a literature review with a critical appraisal method, analyzing 14 studies published between 2017-2022. Journals were selected based on their relevance to the EMR theme in healthcare facilities. The critical appraisal process validated the validity, results, and relevance of scientific evidence to address the methodology and mind mapping for the literature review. Journals were filtered using inclusion and exclusion criteria, and thematic analysis was conducted to identify factors influencing the effectiveness of EMR implementation. A total of 14 studies were included in this literature review. Analysis and synthesis revealed that barriers and strategies for EMR implementation from an HR perspective can be categorized into six aspects: management support, knowledge and skills regarding EMR, organizational culture, user characteristics, and user perspectives. Successful EMR implementation requires active collaboration between management, users, and supporting parties, with ongoing support to address barriers and enhance technology adoption.